1986
DOI: 10.1901/jaba.1986.19-283
|View full text |Cite
|
Sign up to set email alerts
|

Trained, Generalized, and Collateral Behavior Changes of Preschool Children Receiving Gross‐motor Skills Training

Abstract: Three preschool children participated in a behavioral training program to improve their grossmotor skills. Ten target behaviors were measured in the training setting to assess direct effects of the program. Generalization probes for two gross-motor behaviors, one fine-motor skill, and two social behaviors were conducted in other settings. Results indicated that the training program improved the gross-motor skills trained and that improvements sometimes generalized to other settings. Contrary to suggestions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Furthermore, for 4 of 6 participants, it took fewer sessions to reach mastery criterion with the self-instruction procedure than without it. Previous studies have demonstrated that selfinstruction can improve performance of various complex tasks (Duarte & Baer, 1994;Fjellstrom et al, 1988;Grote et al, 1996;Kirby & Holborn, 1986;Risley & Hart, 1968;Rogers-Warren & Baer, 1976). The present study demonstrated that self-instruction could increase the acquisition rate (mean number of sessions to the mastery criterion) of new complex gross-motor chains.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Furthermore, for 4 of 6 participants, it took fewer sessions to reach mastery criterion with the self-instruction procedure than without it. Previous studies have demonstrated that selfinstruction can improve performance of various complex tasks (Duarte & Baer, 1994;Fjellstrom et al, 1988;Grote et al, 1996;Kirby & Holborn, 1986;Risley & Hart, 1968;Rogers-Warren & Baer, 1976). The present study demonstrated that self-instruction could increase the acquisition rate (mean number of sessions to the mastery criterion) of new complex gross-motor chains.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have not routinely presented a direct measure of this response (Duarte & Baer, 1994;Fjellstrom et al, 1988;Freidling & O'Leary, 1979;Grote et al, 1996;Guevremont et al, 1988;Higa et al, 1978;Kirby & Holborn, 1986). Of those studies that measured the self-instruction response, several presented group measures (Higa et al;Risley & Hart, 1968;Rogers-Warren & Baer, 1976), and only one measured individual responding (Grote et al).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations